Pengembangan Modul Ajar Biologi dengan Pendekatan STEAM Berbasis EDP - saufiatun, saufiatun (UNIVERSITAS HAMZANWADI, 2024)
This study aims to: (1) Develop a biology teaching module with a STEAM approach based on the Engineering Design Process (EDP) to improve students’ creative thinking skills. (2) To examine the feasibility and ideality of a biology teaching module with a STEAM approach based on the Engineering Design Process (EDP) to improve students' creative thinking skills. (3) To determine the effectiveness of a biology teaching module with a STEAM approach based on the Engineering Design Process (EDP) to improve students' creative thinking skills. This development research usedthe Borg and Gall model which was carried out with 7 stages of development; initial information collection, planning, initial product development, small-scale trials, product revision, limited trials, and product revision. The subjects of the trial in this study were material experts I and II, design experts, 20 students of SMAS NWDI Tebaban, and 65 students of SMAN 1 Pringgasela. The data collection technique was carried out using a questionnaire and the data was analyzed using quantitative descriptive analysis techniques. Based on the results of data analysis and discussion, it can be concluded that the biology teaching module product with the STEAM approach based on the Engineering Design Process (EDP) to improve students' creative thinking skills is feasible, ideal and effective to be used during the learning process. This feasibility can be seen from the average percentage of feasibility from material expert I 95.14%, material expert II 93.06%, design expert 94.29%, and student response 79%. This has the criteria of very feasible and feasible. Furthermore, the ideality of the teaching module can be seen from the average score of ideality from material expert I 64, material expert II 63, design expert 81, and student response 54.05. This has the criteria of very ideal and ideal. Then the effectiveness of the teaching module can be seen from the average N-Gain obtained from the limited scale of the experimental class 0.62 and the limited scale of the control class 0.26. Based on the average N-Gain obtained, it has moderate criteria with a fairly effective level of effectiveness. Based on the results of the average percentage of the acquisition of Student Worksheets with the STEAM approach Based on Engineering Design Processes (EDP) per group, it shows that Student Worksheets with the STEAM approach Based on Engineering Design Processes (EDP) to improve students' creative thinking skills are in the very creative category.